What’s in your card? The impact of online food delivery apps on depression and eating behaviors - Ozlu Karahan, Tugce; Cakmakci, Dila; Kurtoglu, Eylül; Kul, Zeynep; Kidan, Irem Sevim; Kenger, Emre Batuhan (Frontiers in Nutrition, 2025)
IntroductionDigitalization, through smartphones and online platforms, has become deeply embedded in daily life, beginning to exert significant effects on eating habits and psychological health. Online food delivery (OFD) applications (app) provide easy access to fast food and processed products, exposing individuals to a constant digital food environment. Examining the relationship of these applications with eating behaviors and conditions such as depression is particularly important in the context of increasing mental health problems among young adults. This study aims to examine the relationship between the frequency of use of OFD apps and user attitudes toward these apps, with depression level and eating behaviors in young adults.MethodsParticipants’ demographic information, frequency of use of OFD apps, and attitudes toward these apps were determined by questionnaire questions; depression status was assessed using the Beck Depression Inventory; and eating behaviors were assessed using the Three-Factor Eating Scale (TFEQ-R21).ResultsA total of 383 young adults aged 18–35 years participated in our study. The group with the lowest frequency of OFD apps use (21.2 ± 0.4) had significantly lower uncontrolled eating scores than the other groups (23.4 ± 0.7 and 23.3 ± 0.6; p = 0.005). In addition, a significant decrease in cognitive restraint levels was observed as the frequency of OFD apps use increased (p = 0.031). In addition, depression scores of individuals with more OFD apps (4–6) on their phones (14.1 ± 1.3) were found to be higher than those of individuals who did not use any apps (8.8 ± 1.4; p = 0.025).DiscussionThe findings of our study suggest that the digital food environment can be a determinant not only of individuals’ physical health but also of their psychological health and behavioral eating habits.